Study on a Mid-Temperature Trough Solar Collector with Multisurface Concentration - Zhengliang Li; Mingxian Chen; Husheng Meng; Zehui Chang; Hongfei Zheng (International Journal of Photoenergy)
A new trough solar concentrator which is composed of multiple reflection surfaces is developed in this paper. The concentrator was analyzed firstly by using optical software. The variation curves of the collecting efficiency affected by tracking error and the deviation angle were given out. It is found that the deviation tolerance for the collector tracking system is about 8 degrees when the receiver is a 90 mm flat. The trough solar concentrators were tested under real weather conditions. The experiment results indicate that, the new solar concentrator was validated to have relative good collecting efficiency, which can be more than 45 percent when it operated in more 145°C. It also has the characteristics of rdust, wind, and snow resistance and low tracking precision requirements.